Answer:
X = 4 & Y = 3
Step-by-step explanation:
1. Multiply the first equation by -2 & Multiply the second equation by 1
-2 (2x+3y=17)
1 (3x+6y=30)
Becomes:
−4x−6y=−34
3x+6y=30
Add these equations to eliminate y:
−x=−4
2. Then solve −x= −4 for x:
−x=−4
-x/−1 = −4/−1
(Divide both sides by -1)
x=4
Now that we've found x, plug it back in to solve for y.
Write down an original equation:
2x+3y=17
Substitute (4) for (x) in 2x+3y=17:
(2)(4)+3y=17
3y+8=17(Simplify both sides of the equation)
3y+8+−8=17+−8(Add -8 to both sides)
3y=9
3y/3 = 9/3
(Divide both sides by 3)
y=3
Answer:
k = -2.
Step-by-step explanation:
5(3 - 2k) = 2k + 39 Distribute the 5 over the parentheses:
15 - 10k = 2k + 39
15 - 39 = 2k + 10k
12k = -24
k = -2.
Answer:
20.6
Step-by-step explanation:
Given data
J(-1, 5)
K(4, 5), and
L(4, -2)
Required
The perimeter of the traingle
Let us find the distance between the vertices
J(-1, 5) amd
K(4, 5)
The expression for the distance between two coordinates is given as
d=√((x_2-x_1)²+(y_2-y_1)²)
substitute
d=√((4+1)²+(5-5)²)
d=√5²
d= √25
d= 5
Let us find the distance between the vertices
K(4, 5), and
L(4, -2)
The expression for the distance between two coordinates is given as
d=√((x_2-x_1)²+(y_2-y_1)²)
substitute
d=√((4-4)²+(-2-5)²)
d=√-7²
d= √49
d= 7
Let us find the distance between the vertices
L(4, -2) and
J(-1, 5)
The expression for the distance between two coordinates is given as
d=√((x_2-x_1)²+(y_2-y_1)²)
substitute
d=√((-1-4)²+(5+2)²)
d=√-5²+7²
d= √25+49
d= √74
d=8.6
Hence the total length of the triangle is
=5+7+8.6
=20.6
Answer:
a is the value of X
Step-by-step explanation: